2023
DOI: 10.3390/medicina59030495
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of INHBA Overexpression with Pathological Features, Antitumor Immune Response and Clinical Prognosis in Cervical Cancer

Abstract: Background and Objectives: Cervical cancer (CC) is a malignant tumor occurring in the cervical epithelium, which is one of the most common cancer-caused deaths in females. Inhibin β A (INHBA) is the most widely expressed biomarker of the transforming growth factor-β (TGF-β) family in tumor cells, and has predictive value for tumor development and prognosis. In this study, the expression of INHBA in CC tissue was examined to analyze the relationship between INHBA expression and pathological characteristics, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“… 12 Zeng et al reported that elevated expression of INHBA in CCa patients was correlated with pathological characteristics, anti-tumor immune response, and reduced survival time, resulting in a poor prognosis. 13 Therefore, INHBA is considered as an oncogene, and its high expression is closely associated with poor patient survival.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Zeng et al reported that elevated expression of INHBA in CCa patients was correlated with pathological characteristics, anti-tumor immune response, and reduced survival time, resulting in a poor prognosis. 13 Therefore, INHBA is considered as an oncogene, and its high expression is closely associated with poor patient survival.…”
Section: Discussionmentioning
confidence: 99%